Mechanism of Murabaha Financing Collateral Confiscation Problematic in Islamic Perspective - Sulistyowati; Indy Zakiyatun Nabila; Claudya Ananda Sagita (Faculty of Islamic Economics and Business, UIN Prof. K. H. Saifuddin Zuhri Purwokerto, 2025)
From an Islamic point of view, the murabaha financing collateral confiscation mechanism is problematic. One of the main products of Islamic banking is murabaha capital, which involves a transaction agreement with a profit agreement between the bank and the client. However, payment problems often occur in practice, which requires banks to consider collateral seizure. This study examines the Shariah principles in collateral foreclosure by relying on the Qur'an, Hadith, and fatwa appeals from the National Shariah Council (DSN). The results show that Islamic foreclosure mechanisms should be based on the principles of justice, avoiding unjust actions, and prioritizing the process of mediation and peaceful conflict resolution before resorting to the law. Forfeiture is only permitted if the customer does not show good faith in fulfilling its obligations, and must be proportional to prevent harm to either party. This study found that collateral confiscation can be applied in Shariah-compliant murabaha financing and ensures the proces is fair and ethical according to Islamic principles.